Physiology, psychoacoustics and cognition in normal and impaired hearing - Dijk, Pim van; Başkent, Deniz; Gaudrain, Etienne; de Kleine, Emile; Wagner, Anita Ewa; Lanting, Cris (Advances in Experimental Medicine and Biology, 2016)
The International Symposium on Hearing is a prestigious,triennial gathering where world-class scientists present and discuss the most recent advances in the field of human and animal hearing research. The 2015 edition will particularly focus on integrative approaches linking physiological, psychophysical and cognitive aspects of normal and impaired hearing. Like previous editions, the proceedings will contain about 50 chapters ranging from basic to applied research, and of interest to neuroscientists, psychologists, audiologists, engineers, otolaryngologists, and artificial intelligent researchers